Depositors' Welfare, Deposit Insurance, and Deregulation: Discussion - Heinkel, Robert (Journal of Finance, 1985)
Robert Heinkel, Depositors' Welfare, Deposit Insurance, and Deregulation: Discussion, The Journal of Finance, Vol. 40, No. 3, Papers and Proceedings of the Forty-Third Annual Meeting American Finance Association, Dallas, Texas, December 28-30, 1984 (Jul., 1985), p. 975